2020
DOI: 10.1007/s00268-020-05407-3
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Preoperative Plasma Fibrinogen and Neutrophil‐to‐Lymphocyte Ratio (the F‐NLR Score) as a Prognostic Marker of Locally Advanced Rectal Cancer Following Preoperative Chemoradiotherapy

Abstract: Background Coagulation and inflammation play important roles in tumor progression. This study aimed to explore the prognostic impact of combined analysis of fibrinogen and neutrophil‐to‐lymphocyte (NLR) ratio (F‐NLR score) in locally advanced rectal cancer (LARC) receiving preoperative chemoradiotherapy (pCRT) and radical surgery. Method Totally 317 patients were included. X‐tile analysis was used to determine the optimal cutoff values of preoperative fibrinogen and NLR. F‐NLR scores were defined as 2 (both hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…Many studies have shown that an elevated FAR is closely related to a poor prognosis in various cancers. 37 To the best of our knowledge, our study is the first to report on the prognostic role of the FAR in Pan-NENs.…”
Section: Discussionmentioning
confidence: 74%
“…Many studies have shown that an elevated FAR is closely related to a poor prognosis in various cancers. 37 To the best of our knowledge, our study is the first to report on the prognostic role of the FAR in Pan-NENs.…”
Section: Discussionmentioning
confidence: 74%
“…For instance, a combination of clinical risk factors and radiomics features emphasized potential advantages to the individualized preoperative prediction of lymph node metastasis in CRC patients, which was proposed to benefit patient OS. Sun et al argued that the fibrinogen and neutrophil‐to‐lymphocyte ratio (F‐NLR score) is a promising predictor for disease relapse in rectal cancer patients 25,26 . The dissertations mentioned above were dedicated to predicting the preoperative or postoperative conditions of patients, and both might improve the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the distance of the lower tumor margin to the anal verge is undoubtedly an important independent factor for the determination of sphincterpreserving procedure. According to Sun et al rectal cancer with a distance of the tumor from the anal verge of > 5 cm was shown to have a significant higher rate of sphincter-preservation [13]. Due to conflicting results between pre-treatment CT, MRT and rigid proctoscopy we decided not to incorporate the distance to the anal verge exactly.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple studies [7,8,13], the serum fibrinogen value proved to be a promising independent predictor of the therapeutic response and the prognosis after nRCT. Until now, we have not had any data to show whether this parameter also influences the sphincter-preserving surgery rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation